2006
DOI: 10.1021/ie050882g
|View full text |Cite
|
Sign up to set email alerts
|

Removal of n-Butyl Mercaptan Using Stripping with an Inert Gas:  A Nonequilibrium Approach via Mass Balances

Abstract: The stripping of n-butyl mercaptan (RSH) from neutral and alkaline aqueous solution with gaseous nitrogen is investigated at ambient temperature and pressure in a semibatch system. A model considering the dynamic state, the thiol mass balance, the effect of RSH dissociation, and the deviation from chemical equilibrium is developed and solved numerically. The assumption of chemical equilibrium between undissociated thiol and its ion (RS -) is valid at neutral pH, but at alkaline conditions, RS -f RSH is the rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The VOSC concentrations in the bioreactor decreased with increased flow rate of N 2 (Figure A–C) and showed that thiols can be effectively stripped by applying a low volumetric flow rate of an inert gas. Moreover, it can be observed that the sum of VOSCs in the bioreactor headspace decreased with increasing thiol hydrophobicity (Figure A–C) …”
Section: Results and Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The VOSC concentrations in the bioreactor decreased with increased flow rate of N 2 (Figure A–C) and showed that thiols can be effectively stripped by applying a low volumetric flow rate of an inert gas. Moreover, it can be observed that the sum of VOSCs in the bioreactor headspace decreased with increasing thiol hydrophobicity (Figure A–C) …”
Section: Results and Discussionmentioning
confidence: 95%
“…Moreover, it can be observed that the sum of VOSCs in the bioreactor headspace decreased with increasing thiol hydrophobicity (Figure 3A− C). 33 A lower selectivity for sulfur production was found at higher VOSC concentrations. Probably this resulted from the inhibitory effects of VOSCs on the overall biological sulfide oxidation rate 12,19 which in turn, leads to an increasing abiotic formation of polysulfide anions causing spontaneous thiosulfate formation.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The nonequilibrium unsteady-state mass balance model includes mass balance in liquid phase of neutral and ionic form of n-butyl mercaptan, electroneutrality condition, water equilibrium in liquid and gas phase and a set of initial conditions. This model is described in detail elsewhere [7].…”
Section: Mathematical Model Of the Stripping System Based On Mass Balmentioning
confidence: 99%